Сerebral allergy in children - V. M. Studenikin; N. I. Studenikina (Лечащий Врач)
The article focuses on cerebral allergy (CA), described in the middle of 20th century. The evolution of subsequent notions about CA and some relevant definitions are provided. Mechanisms of CA are outlined along with the data concerning pyrroles and pyroluria. Main neurologic and psychiatric manifestations of CA and pyroluria are described, along with treatment approaches.